SDGs, the Green Economy and Finance, and the Role of MSMEs. - Sazir Nsubuga Mayanj (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
Humankind inherently desires a better life than that being enjoyed at a particular time. To achieve this, resources from the environment, which are unfortunately finite are exploited. Meanwhile, the population, if not deliberately controlled, or reduced by disasters such as earthquakes and diseases, can grow in geometric progression. In an organized society, the resources are exploited through MSMEs (micro-small and medium enterprises). These dominate production and distribution processes for products and delivery of services. The author argues that despite the important roles in economies regardless of whether they are developed or not, MSMEs also contribute to a great extent to the destruction of the environment, which ironically supports their activities. Among efforts by the global community to address the threat to the environment posed by humans through their MSMEs are the Millennium Development Goals (MDGs) and then replaced by the seventeen Sustainable Development Goals (SDGs), which are expected to be achieved by 2030.